Triptonide Protects against Doxorubicin-induced Cardiotoxicity in Rats by Regulating Oxidative Stress and Cardiac Biomarkers - Dong, Lizhao; Liu, Hongxuan (Indian Journal of Pharmaceutical Education and Research, 2023)
Background: Doxorubicin is an anthracycline anti-cancer drug and one of the most widely used chemotherapeutic medications to treat both solid and hematological tumors. However, due to the major adverse effect of cardiotoxicity, the clinical use of doxorubicin was highly restricted. Objectives: The current research was undertaken to explore the salutary properties of the triptonide on the doxorubicin-induced cardiotoxicity in rats. Materials and Methods: Rats were given 2.5 mg/kg of doxorubicin to produce cardiotoxicity, which was then treated with 25 mg/kg of triptonide. A set of rats was treated with 50 mg/kg of triptonide alone. Plethysmography on the tail-cuff was used to measure the blood pressure indicators. Using assay kits, the concentrations of oxidative and antioxidative biomarkers and cardiac function markers were measured. Using established techniques, the antioxidant enzyme activity was assessed. The histopathological study was performed on the heart tissues to analyze the doxorubicin-induced histological changes. Results: The heart weight was improved by triptonide treatment in the doxorubicin-induced rats. Triptonide effectively reduced the blood pressure indicators in the doxorubicin-induced rats. In the doxorubicin-induced rats, triptonide significantly decreased the LDH, CK, and AST activities and the status of myoglobin, H-FABP, GP-BB, and CK-MB. The triptonide therapy decreased the levels of INF-γ, MCP-1, and TGF-β in the serum of doxorubicin-induced rats. The findings of the histopathological examination showed that triptonide had therapeutic benefits. Conclusion: In summary, the results of this study supported the hypothesis that triptonide could ameliorate the biochemical and histological changes in the rats' hearts that were caused by doxorubicin.
Keywords: Creatine kinase; Cardiac damage; Myoglobulin; Doxorubucin; Triptonide